Systematics of the Sierra Nevada endemic earwig: Eulithinus analis (Forficulidae, Dermaptera) - Puerta-Rodríguez, Leticia; Jurado-Angulo, Pilar; Jiménez-Ruiz, Yolanda; Rosas-Ramos, Natalia; García-París, Mario (European Journal of Taxonomy, 2024)
Since the description of Eulithinus analis (Rambur, 1838) the taxonomic position of this Sierra Nevada endemic earwig has been controversial. It has been subdivided in different taxa, assigned to various genera or transferred to different subfamilies. With the aim of clarifying its systematics, we performed a mitochondrial phylogeographic analysis using specimens from different localities of Sierra Nevada representing the diverse phenotypes treated as differentiated taxa until now, and a phylogenetic analysis including representatives of apparently distant, but morphologically close, relatives. The phylogenetic and phylogeographic results obtained using mitochondrial (cytb, cox1) and nuclear (ITS2) markers and the study of morphological characters, indicate that the Sierra Nevada Mountain Range harbors a single species of the genus Eulithinus. Based on these molecular data, the morphological characters used to date in the internal taxonomy of this group of earwigs, especially size and shape of the cerci, lack diagnostic validity and show a large inter- and intra-populational variability. These results imply the synonymy of Eulithinus montanus (Steinmann, 1981) with Eulithinus analis (Rambur, 1838) syn. nov. and the reconsideration of Eulithinus analis outside the subfamily Allodahliinae. We established the synonymy between Eulithinus analis (Rambur, 1838) and Forficula brevis Rambur, 1838 syn. nov., a name that must be removed from the synonymy of Forficula decipiens Gené, 1832.